Analysis of the Industry’s Perspective on Digital Competence Vocational Human Resources - Mia Rahma Romadona; Andi Budiansyah; Suryadi Suryadi; Maulana Akbar; Fachrizal Fachrizal; Syahrizal Maulana; Ratna Sri Harjanti; Arif Hidayat (STI Policy and Management Journal, 2026)
Industry in the technological era, as an economic driver is highly dependent on resource management especially human resources. Vocational higher education graduates (Diploma 3 and 4/applied bachelor levels) are designed to be ready with specific competency aligned to labor market demands. However, industries continue to report challenges in recruiting vocational graduates who fully their need. This study evaluates the digital competencies of vocational graduates in Indonesia in relation to industry using the European Commission’s Digital Competence Framework (DigComp). A mixed-method design was employed, combining in-depth interview and an online survey in eight digitally oriented companies in Indonesia which was then processed using descriptive statistics and paired sample t-tests. The results show not statistically significant difference (p > 0.05) between industry expectations and graduates’ competencies across the five DigComp dimensions: information digital literacy, communication and collaboration, content creation, security, and problem solving. Further results, graduates can meet technical standards but face recruitment barriers due to deficiencies in soft skills like communication, teamwork, and negotiation. These results confirm the applicability of DigComp in the context of vocational education in Indonesia, but also highlight the need to integrate generic competencies and strengthen structured industry collaboration to support long-term digital workforce development in Indonesia.